Ibsen in Russia Revisited: The Ibsenian Legacy in the Writings of the Russian Symbolist Andrey Bely - Helle, Lillian Jorunn (Poljarnyj vestnik, 2016)
The intellectual atmosphere of Russian fin de siècle was characterized by a strong fascination for Norway, its nature, its culture and its literature. A good example is Henrik Ibsen who was a significant source of inspiration for Russian dramatists, writers and poets. The Russian symbolists in particular saw Ibsen as a tutelary spirit and not least the “younger” symbolist Andrey Bely regarded his works and thoughts as a prefiguration and a foreshadowing of his own. Ibsen was important to Bely through all his various stages of intellectual, artistic and spiritual seeking and in accordance with Bely’s highly interpretative, hermeneutical approach to the world, in which everything he experienced was transformed to confirm his own symbolist Weltanschauung, also Ibsen was transformed in much the same manner. And the very intriguing way in which Bely rewrites the Norwegian playwright into his own writings will be the main topic of this article, illustrating how the Russian symbolist refigures the Norwegian dramatist to make him fit into his own continuous search for new and meaningful perspectives and positions. Moreover and even still more remarkable, this search convincingly demonstrates how the Ibsenian legacy throughout the many different phases of Bely’s creative development keeps it crucial place within Bely’s life cycle, thereby establishing a most interesting thread in the complex web of Ibsen’s Wirkungsgeschichte.